Starch fraction profiles of milled, nonparboiled rice varieties from Nigeria. (22nd July 2013) - Odenigbo, Amaka M.; Ngadi, Michael; Manful, John; Danbaba, Nahemiah
Summary: This study determined the levels of nutritionally important starch fractions in selected milled, nonparboiled rice cultivated in Nigeria. Five improved varieties ( FARO 52, FARO 57, FARO 44, FARO 60 and FARO 61 ) and four local varieties ( Kwandala, Yardass, Jeep and Jamila ) were evaluated. There were significant differences in starch fractions among varieties. Resistant starch (RS) ranged between 1.43% and 3.13%. Rapidly digestible starch (RDS) was lowest in Jamila (27.70%) and highest in FARO 61 (39.26%). Generally, the local varieties had significant higher RS (2.71%) with a lower RDS (32.82%) compared with improved varieties (RS; 1.88% and RDS; 36.07%). RS was inversely related to RDS and starch digestion index (SDI). The SDI had a highly significant positive correlation with RDS ( r  = 0.879, P  < 0.01). These results highlight the need for further work in the identification of milled, nonparboiled rice varieties with less rapid digestion for its associated health benefits to consumers.